Panel Discussion: Sustainable Engineering for 21St Century and Beyond. Issue 25 (2019) - Hersh, Marion; Stapleton, Larry; Kopacek, Peter; Groumpos, Peter; Kent, Mary Doyle; Fanning, Michael; Costello, Orlagh
Abstract: The panel discussion involves the organisers and one author from each of four papers presented in a session on engineering ethics, emerging challenges and socio-cultural effects. The papers consider a wide range of issues of great importance to the engineering community and beyond it to the population as a whole. They include the contribution of engineering to sustainable development, the need for more women engineers, roboethics and the development of a low cost robotic arm to support independence. The discussion will involve the audience in further consideration of the issues raised in the session and enable them to both make contributions and put questions to the panel.